Ceramica e piccoli oggetti dallo scavo della Chiesa del Reliquiario ad Umm al-Rasas - Pappalardo, C. (Liber Annuus, 2006)
Abstract The brief comment looks at the most noteworthy ceramics and objects, discovered in the two tombs of the “Reliquary” Church of Umm al-Rasas, with the completion of the excavations of the summer campaign of 2004. The ceramic fragments with sketches and descriptions, originate from the layers above the pavement level and from the surveys carried out at the level of the mosaic. In harmony with the situation of the layers and homogenous to that of the other churches excavated at Umm al-Rasas, after a period of abandonment the building may have been partially used as a dwelling before the ultimate structural collapse. The two tombs discovered near the western angle of the northern nave and near the eastern angle of the southern nave, contained the bones of more than one individual, buried at different times. Lastly, together with a pair of rings, a cross and various fragments of a pearl necklace of vitreous glass, the discovery was also made of a pair of earrings, a hair pin and an iron belt buckle, objects which came from the poor burial chests belonging to the dead.